Synthesis and Characterization of New Class of Mixed Polysulfide Ligands of Chromium (III) Complexes - Abdullah, M. A. (Sulaimani Journal for Pure and Applied Sciences, 2002)
From the facile loss of coordinated Sulfur to chromium (Cr-S) and via intermolecular insertion reaction accompanied by elimination reaction two different chromium (III) complexes; binuclear, pu-(bis L-cysteineato(S-S)disulfide) bis [(mo) allyl - L- cysteineto (N,O,S) chromium (III)], [Cr2 (C3H5O2NS)2 (C3H6)2 (C6H10O4N2S4)] and sodium dihydroxobis(S-methyldisulfide L-cysteinato)chromate (III) Na (Cr(OH)2- (C4H8O2 NS3)2 ) have been synthesised and characterized by UV- visible 1R and NMR spectroscopic methods and elemental analysis techniques.
Keywords: Chromium III complex; polysulfide